THE EFFECT OF AUDIT EXPERIENCE, PROFESSIONAL Skepticism And INDEPENDENCE ON THE AUDITOR'S ABILITY IN DETECTING FRAUD (Empirical Study On A Public Accounting Firm In Jakarta) - Parso (Jurnal Mantik, 2022)
This study aims to determine the effect of audit experience, professional skepticism, and independence simultaneously on the auditor's ability to detect fraud. This study uses quantitative methods and primary data, namely questionnaires from Public Accounting Firm. The sample used is the convenience sampling method, with 100 respondents. The data analysis technique uses a Validity Test, Reliability Test, Normality Test, Multicollinearity, Heteroscedasticity, Autocorrelation, Multiple Linear Test, T-Test, F Test, and Coefficient of Determination. The result of this research is that experience significantly affects the auditor's ability to detect fraud. Professional Skepticism significantly affects the auditor's ability to detect fraud. Independence significantly affects the auditor's ability to detect fraud.